Classification of the lexicon of modern Polish according to the structure of consonant clusters - Dziubalska-Kołaczyk, Katarzyna; Jankowski, Michał; Wierzchoń, Piotr (Proceedings of the 17th ICPhS, Hong Kong 2011, 2011)
The aim of the project this paper reports on is to identify and analyze the correlation between Polish consonant clusters and the semantic categories of the words that contain a given cluster. The material studied is a large corpus of Polish newspapaper text. A common characteristic of sets of words is whether or not they contain an identical consonant cluster, which understood here as a contiguous string of consonants not interrupted by a vowel. The aim of the study is to find other common characteristics of the words, that is the identification and analysis of a correlation between the cluster and the semantic categories that the words containing the cluster belong to. The semantic categories considered in the model pertain to the following properties of the words featuring a common cluster: derivation, part of speech, inflection, and morphotactics.
Keywords: consonant cluster; frequency; ontology; Polish language; phono-morpho-semantics